(untitled) (Research, Society and Development, 2024)
Potentially Malignant Oral Disorders (POMD) are clinical conditions that present a high risk of transformation into oral cancer, especially squamous cell carcinoma (SCC). This study aimed to develop a manual that will enable the clinical diagnosis of potentially malignant oral disorders (DOPM) and their clinicopathological correlations, highlighting the main aspects that help in the early identification and adequate treatment of these conditions. Documentary research was carried out using an indirect, descriptive source, qualitative, and narrative literature review type. One way to prevent this is early diagnosis of the injury, and with it the necessary management is possible, once diagnosed early on, progression is prevented. Oral cancer, whose incidence has increased globally, has smoking, alcohol consumption, and viral infections as risk factors. The DOPM with malignant potential mentioned in this study are: Leukoplakia, Erythroplasia, Lichen planus, Submucous Fibrosis, and Actinic Cheilitis, all of which have cellular changes that can progress to malignancy.